Primary hepatic aspergillosis following induction chemotherapy for acute leukemia. Issue 5 (27th August 2013) - Chasan, R.; Patel, G.; Malone, A.; Finn, M.; Huprikar, S.
Abstract: Invasive aspergillosis (IA) contributes significantly to the burden of infectious complications in heavily immunosuppressed patients with acute leukemia. The infection is typically acquired via inhalation into the respiratory tract, and the lungs are most commonly involved. However, disseminated disease may occur and reports of isolated extrapulmonary infection suggest the gastrointestinal tract is likely an additional portal of entry for this organism. We describe a case of primary hepatic aspergillosis in a patient with acute myelogenous leukemia. The patient did not respond to medical therapy with antifungals and ultimately required surgical exploration and drainage. IA should be considered in an immunosuppressed patient with hepatic abscesses and may require a combined surgical and medical approach to therapy.